Inserção profissional dos licenciados em Direito : da formação académica ao acesso às profissões reguladas - Santos, Mónica (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
The article seeks to understand the transition of Law graduates as a process that id shaped, firstly, by the expansion of Portuguese higher education and the persistence of social inequalities in its entrance and distribution by subsystems and faculties. And secondly, by the entrance mechanisms of regulated professions, in particular, lawyers. The study focuses on a sample of 565 graduates who completed the graduation between the school years 2002/2003 and 2006/2007, and whose academic qualification was obtained in one of the six public and private universities of North Portugal.